2012
DOI: 10.1002/clc.22077
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Warfarin Use for Stroke Prevention in Patients With Atrial Fibrillation in Hong Kong

Abstract: Background:Oral anticoagulation medications such as warfarin reduce the risk of stroke in atrial fibrillation (AF) but have been underutilized. This study aimed to investigate physicians' perceptions of stroke prevention management and patients' knowledge of AF and warfarin therapy in Hong Kong (HK).Hypothesis:Both physician and patient's knowledge on warfarin use were the barriers for stroke prevention in patients with atrial fibrillation in Hong Kong.Methods:This prospective survey‐based study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 16 publications
4
32
0
1
Order By: Relevance
“…This study demonstrated that physician’s choice was the most important reason, followed by patient refusal. A large number of doctors lacked knowledge concerning the management of AF and knew less about anticoagulation therapy 20. Also, the majority of physicians feared the bleeding risk related to warfarin, which was likely to lead to conflicts between doctors and patients 21,22.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that physician’s choice was the most important reason, followed by patient refusal. A large number of doctors lacked knowledge concerning the management of AF and knew less about anticoagulation therapy 20. Also, the majority of physicians feared the bleeding risk related to warfarin, which was likely to lead to conflicts between doctors and patients 21,22.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, warfarin is extremely underused 9,10 in Chinese patients with AF, particularly in those with a higher stroke risk. 11,12 Besides physicians' compliance with guideline recommendations for stroke prevention, 13 patients' nonadherence and nonpersistence to warfarin are major barriers to improved anticoagulation treatment in patients with AF.…”
mentioning
confidence: 99%
“…There is a large number of stroke risk factors identified among AF patients; hence, an individual patient's risk will depend largely on the combination of risk factors, rather than from simply being an AF patient. Permutations of these risk factors have been used to formulate stroke risk‐stratification schemes, with the initial objective of identifying high‐risk patients to be targeted for OAC using an “inconvenient” drug, warfarin …”
Section: Stroke Riskmentioning
confidence: 99%
“…Permutations of these risk factors have been used to formulate stroke risk-stratification schemes, with the initial objective of identifying high-risk patients to be targeted for OAC using an ''inconvenient'' drug, warfarin. 7,8 The derivation of stroke risk-stratification schemes depends on identification of common risk factors, which importantly have been defined and recorded in derivation 634 Clin. Cardiol.…”
Section: Stroke Riskmentioning
confidence: 99%